Troxerutin suppress inflammation response and oxidative stress in jellyfish dermatitis by activating Nrf2/HO-1 signaling pathway - Liu, Ran; Wang, Yulian; Kuai, Wenhao; Li, Wenting; Wang, Zengfa; Xiao, Liang; Wu, Jianhua (Frontiers in Immunology, 2024)
Stomolophus meleagris envenomation causes severe cutaneous symptoms known as jellyfish dermatitis. The potential molecule mechanisms and treatment efficiency of dermatitis remain elusive because of the complicated venom components. The biological activity of Troxerutin (TRX) was firstly examined as a potential treatment for jellyfish dermatitis. Here, we examined the toxic effects of the tentacle extract (TE) obtained from S. meleagris in vivo and in vitro, probed the altered activity of relevant signaling pathways, and detected the protective effects of TRX against the inflammation and oxidative damage caused by TE. The results suggested that TE significantly induced the accumulation of inflammatory cytokines and reactive oxygen species. Moreover, a robust increase in the phosphorylation of mitogen-activated protein kinase (MAPKs) and nuclear factor-kappa B (NF-κB) signaling pathways was observed. While, the acute cutaneous inflammation and oxidative stress induced by TE were significantly ameliorated by TRX treatment. Notablly, TRX suppressed the phosphorylation of MAPK and NF-κB by initiating the nuclear factor erythroid 2-related factor 2 signaling pathway, which result in decreasing inflammatory cytokine release. These consideration shown that TRX may be a potential medicine that inhibits the major signaling pathway responsible for inducing inflammatory and oxidative damage of jellyfish dermatitis, offering a novel therapy in clinical applications.